Routledge handbook of critical terrorism studies - Jackson, Richard (Routledge, Taylor & Francis Group, 2016)
This new handbook is a comprehensive collection of cutting-edge essays that investigate the contribution of critical terrorism studies to our understanding of contemporary terrorism and counterterrorism. Covering a wide range of topics, including key debates in the field and emerging issues, the Routledge Handbook of Critical Terrorism Studies will set a benchmark for future research on terrorism and the response to it. This handbook will be of great interest to students of terrorism studies, political violence, critical security studies, and IR in general.